Redox Reaction between Main‐Group Elements (Te, Sn, Bi) and N‐Heterocyclic‐Carbene‐Derived Selenium Halides: A Facile Method for the Preparation of Monomeric Halides. Issue 30 (4th September 2013) - Manjare, Sudesh T.; Yadav, Sangeeta; Singh, Harkesh B.; Butcher, Ray J.
Abstract: The synthesis and characterization of substituted benzimidazolin‐2‐selones (4c –4d ) and ‐tellone (4i ) are reported. Upon reaction with halogens (I2, Br2, and Cl2 ), these selones and tellone yield dihaloselones/tellone (5c –5i ). The reaction of dihaloselones with elemental tellurium/tin/bismuth leads to the formation of selone‐coordinated monomeric tellurium tetrahalides, tellurium dibromide (8 ), tin tetrahalides, and bismuth triiodide adducts (7a –7g ), respectively. The structures of the tellurium tetrahalide (7a, 7d, and7g ), tellurium dibromide (8 ), tin tetrahalide, and bismuth triiodide adducts have been established by single‐crystal X‐ray analysis. The bismuth triiodide adduct is the first neutral tetrameric structure with selones. The bismuth adduct has been used as a single‐source precursor for the synthesis of bismuth selenide (Bi2 Se3 ) nanoparticles, which were characterized by powder XRD patterns. The TEM images show the hexagonal shape of the nanoparticles. Abstract : The reaction of dihaloselones with elemental tellurium leads to the formation of selone‐ coordinated monomeric tellurium tetrahalides and tellurium dibromide adducts. A plausible mechanism for the formation of tellurium halide adducts is proposed. Tellurium halide adducts are probably an intermediate in the formation of cationic diselenides.